Genetic influence on laterality in schizophrenia?: A twin study of neurological soft signs - Niethammer, Rainer; Weisbrod, Matthias; Schiesser, Steffi; Grothe, Jo; Maier, Sabine; Peter, Uta; Kaufmann, Claudia; Schröder, Johannes; Sauer, Heinrich (The American journal of psychiatry, 2000)
OBJECTIVE: This study explored the genetic basis of neurological soft signs in schizophrenia and addressed disturbed hemispheric lateralization. METHOD: The authors investigated neurological soft signs in 30 monozygotic twin pairs, 13 pairs discordant for schizophrenia or schizoaffective disorder and 17 healthy comparison twin pairs. RESULTS: The twins with schizophrenia showed higher total scores for neurological soft signs than did the comparison subjects. The total scores for neurological soft signs of the nonaffected discordant twins were significantly higher than those of the comparison twins. There was a significant difference between the nonaffected and affected discordant twins in total scores for neurological soft signs. In contrast to the comparison subjects, the nonaffected and affected twins of the discordant pairs showed a trend toward higher scores for neurological soft signs on the left body half. CONCLUSIONS: These results suggest that the occurrence of neurological soft signs and, more specifically, their lateralization to the left body half are genetically transmitted.
Gesehen am 02.06.2021